Child abuse and experiences of discrimination are linked to fear of childbirth among younger patients in the US: a cohort study - Natacha M. De Genna; Rachel P. Kolko Conlon; Meredith Spada; Priya Gopalan (BMC Pregnancy and Childbirth)
Abstract Background Studies have documented more fear of childbirth (FoC) among younger people, resulting in psychological distress, health-risk behaviors, pregnancy termination, and elective Caesarian delivery. Little is known about FoC in the US, particularly among African Americans, despite higher rates of maternal morbidity and mortality. The purpose of this study is to examine FoC in a US sample of pregnant adolescents and young adults. Methods We surveyed FoC as part of a prospective cohort study focused on pregnant people ages 14–21 (n = 147). FoC was assessed online during the third trimester using the Revised Wijma Delivery Expectancy/Experience Questionnaire, a measure adapted for the US (alpha = 0.85). We examined the independent contribution of sociodemographic variables, exposure to trauma, mental health, substance use, and social support on FoC scores. Results Mean age was 19.7 years (SD = 1.7) and the sample was predominantly African American (76%) and heterosexual (63%). In the final regression model, experiences of child abuse, discrimination, stress, and social support were associated with FoC. Conclusions The results of this study highlight pregnancy intentions, experiences of abuse and discrimination, and social support as critically related to FoC among younger patients in the US. Future research is warranted to better understand relationships among these exposures and the potential to address social support to improve pregnancy experiences among young people with FoC. Shifting the focus of care from individual-level attributes associated with health disparities to social determinants of health and contextual factors allows for a health equity-focused population level approach to this vulnerable population.